Covid-19 pandemic: Psychosocial effect among physical and health education staff in Kogi State Nigeria - Olowoleni, Victor; Ayodele, Kolade Babatunde; Olaseyo, Toyosi; Adeola , Moses Folusayo (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
Fear and anxiety have always been a negative affect in performance and job settings, especially when there are external pressures. The Corona virus-19, took the world by surprise just when everybody was enthusiastic about the long-expected year 2020. Movements were restricted, offices, businesses, and public places shut down with imposed curfews allowing only “essential workers” do their jobs. These, invariably affected the way work and associations would later become even after the lockdown. The study aimed to know whether the psychosocial effect of COVID-19 (fear and anxiety) affect physical and health education staff of Kogi State Nigeria. Descriptive survey method was adopted for the research. 200 respondents (male & female) that included physical and health education staff (350) from all higher institutions in Kogi state were part of the study. The average age of respondents was 48.5years. The Fear of COVID-19 Scale (FCV-19S) (α =.74) and the Corona Virus Anxiety Scale (α =.82) was used to collect data. Descriptive statistics of frequency counts, means and percentages were used to analyze data. It is concluded that physical and health education staff in Kogi State do not experience anxiety and fear due to COVID-19. A limitation encountered was most respondents feared been stigmatized with COVID as was the case at the time. It is significant in the sense that employees are greatly influenced by the views of their employer. Further research should be on the attitude of physical and health educators in Kogi State Nigeria to work during COVID-19 pandemic.